Drug Withdrawal Due to Safety: A Review of the Data Supporting Withdrawal Decision - Craveiro, Nuno S.; Lopes, Bruno Silva; Tomás, Lara; Almeida, Sofia Fraga (Current Drug Safety, 2020)
Introduction: Several drugs were withdrawn from the market due to safety. Objective: The aim of this study was to describe data supporting drug withdrawal from the market due to safety reasons in countries belonging to the World Health Organization. Methods: We analyzed drugs withdrawn from the market between 1990 and 2010. All medicine agencies of the countries belonging to the Program for International Drug Monitoring of the World Health Organization were contacted. To complete data, Medline, reference books and available drug databases were also searched. Information sources on which authorities based their withdrawal were categorized and the average time between the first date of exposure and withdrawal was calculated and stratified. Results: A total of 133 drugs that met the inclusion/exclusion criteria were withdrawn from the market due to safety reasons in the period reviewed (1990 - 2010). Hepatotoxicity (n=36, 27.1%), cardiac disorders (n=25, 18.8%), hypersensitivity (n=17, 12.8%) and nephrotoxicity (n=14, 9.8%) were the major reasons responsible for 69.2% of all drugs withdrawn. In most cases, Information Sources for drug withdrawal were spontaneous reports and/or case reports (n=86, 64.7%), followed by clinical trials (n=24, 18.0%). The average time between the introduction of a drug and its withdrawal due to safety reasons was 20.3 years (SD±13.8). Conclusion: According to available and published evidence, there is no gold standard to identify risks associated with drug exposure. These findings strengthen the role of different information sources within the drug safety review process.
Keywords: program for international drug monitoring